Improved split-ubiquitin screening technique to identify surface membrane protein-protein interactions - Daniel Ivanusic; Jürgen J. Heinisch; Magdalena Eschricht; Ulrike Laube; Joachim Denner (BioTechniques)
Yeast-based methods are still the workhorse for the detection of protein-protein interactions (PPIs) in vivo. Yeast two-hybrid (Y2H) systems, however, are limited to screening for a specific group of molecules that interact in a particular cell compartment. For this reason, the split-ubiquitin system (SUS) was developed to allow screening of cDNA libraries of full-length membrane proteins for protein-protein interactions in Saccharomyces cerevisiae. Here we demonstrate that a modification of the widely used membrane SUS involving the transmembrane (TM) domain of the yeast receptor Wsc1 increases the stringency of screening and improves the selectivity for proteins localized in the plasma membrane (PM).